Comprehensive risk assessment of non-typhoon rainstorms over the southeastern coastal region of China - Ye, Jinyu; Zhang, Rongyan; Lin, Guangfa; Zhang, Mingfeng; Gao, Lu (Frontiers in Environmental Science, 2022)
The daily precipitation data (20-20 o'clock) of 66 meteorological stations from 1981 to 2020 were collected. According to the definition of rainstorm day and rainstorm process, 614 non-typhoon rainstorm processes data were obtained after removing the typhoon rainstorm processes data. Combined with the topographic data, the geological disaster points data and the social economic data, this study established an indices system from four aspects: disaster-causing factors, disaster-formative environment, disaster-affected bodies, and disaster prevention and mitigation abilities. Based on the analytic hierarchy process, the entropy method and the correlation coefficient analysis method, the combination weighting was assigned to carry out the non-typhoon rainstorm disaster risk assessment. The results show that the spatial pattern of the comprehensive risk of non-typhoon rainstorm in Fujian Province is completely different from that of typhoon rainstorm in this study area. It shows a gradually increasing trend from the eastern coastal area to the mountainous area in the northwest. The risk areas above middle were observed in the northwestern Fujian and the narrow coastal area of southeastern Fujian. Risk of most of the areas between the two mountain ranges in the middle and northwest of Fujian was relatively lower. The disaster-causing factors were the dominant risk factors of non-typhoon rainstorm. The spatial pattern of non-typhoon rainstorm hazard is obviously affected by the topography of Fujian Province. The comprehensive risk pattern of a specific historical non-typhoon rainstorm case is significantly different from that of the general comprehensive risk of non-typhoon rainstorm disasters. In terms of historical cases, most of the higher-risk and high-risk areas of non-typhoon rainstorm cases were generally small, and were concentrated in northwestern Fujian, but the comprehensive risk pattern of different cases was significantly different.